Dating Violence, Sexual Assault, and Sexual Harassment Victimization Among Girls on an Indian Reservation: An Examination of Rates and Risk and Protective Factors - Edwards, Katie M. (Violence against women, 2022)
We documented the scope and correlates of past 6-month victimization among middle and high school girls on an Indian Reservation. Participants were 102 Native American girls in Grades 6-12. Rates of all forms of past 6-month victimization were higher for high school girls compared with middle school girls. In regression analyses, binge drinking related to higher rates of sexual assault and sexual harassment. Furthermore, connection to culture related to lower rates of sexual harassment, and efficacy to resist a sexual assault was related to lower rates of sexual assault and sexual harassment.